Floral Biodiversity of the Seti Gandaki River, Pokhara Nepal: Phytoplankton Communities - Pokharel, Kishor K (Journal of Natural History Museum, 2015)
Present paper deals with the phytoplankton communities in the Seti Gandaki river, Pokhara, Nepal. It is the pioneer work to explore the above mentioned riverine flora. Altogether 28 genera belonging to 19 families and 5 classes were recorded during the investigation period. There was a decrease in taxa richness from upstream site (19 genera) to the urban site (9 genera) and an increasing trend to the downstream site (15 genera). Myxophyceae, bacillariophyceae and chlorophyceae comprising 10, 9 and 6 genera respectively were predominant classes among the phytoplankton communities. Oscillatoriaceae and nostocaceae; fragilariaceae and achnanthaceae; and zygnemataceae were dominant families among myxophyceae, bacillariophyceae and chlorophyceae respectively. The dominant genera were, Microcystis Kutzing, Oscillatoria Vaucher and Anabaena Bory; Tabellaria Ehrenberg, Achnanthes Bory and Cymbella Agardh; Ulothrix Kutzing and Spirogyra Link; and Peridinium Ehrenberg among myxophyceae, bacillariophyceae, chlorophyceae and dinophyceae respectively. The genera found at all sites were, Tabellaria Ehrenberg, Achnanthes Bory and Cymbella Agardh; and Microcystis Kutzing, Anabaena Bory, Oscillatoria Vaucher and Schizothrix Kutzing among bacillariophyceae and myxophyceae, where as, those occurred only at Site 2 were, Chlamydomonas Ehrenberg, Oedogonium Link, Scenedesmus Meyen and Zygnema Agardh; Euglena Ehrenberg; Fragilaria Lyngbye; Gymnodinium Stein; and Merismopedia Meyne among chlorophyceae, euglinophyceae, bacillariophyceae, dinophyceae and myxophyceae respectively. The decline in taxa richness at the urban site reflects the perturbation of the riverine environment due to urbanization which needs regular monitoring and essential measures to control further deterioration J. Nat. Hist. Mus. Vol. 26, 2012: 203-211